The Sage encyclopedia of educational research, measurement, and evaluation - Frey, Bruce B. (Thousand Oaks, California : SAGE Publications, Inc., 2018)
In an era of curricular changes and experiments and high-stakes testing, educational measurement and evaluation is more important than ever. In addition to expected entries covering the basics of traditional theories and methods, other entries discuss important sociopolitical issues and trends influencing the future of that research and practice. Textbooks, handbooks, monographs and other publications focus on various aspects of educational research, measurement and evaluation, but to date, there exists no major reference guide for students new to the field. This comprehensive work fills that gap, covering traditional areas while pointing the way to future developments.
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Education -- Research -- Methodology